CLINICAL CHARACTERISTICS OF BURNOUT SYNDROME - Faxritdinovna, Yadgarova Nargiza; Shavkatovna, Shadmanova Lola (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: Emotional Burnout Syndrome (EBS) has emerged as a significant concern within healthcare professions, affecting the mental health and performance of medical practitioners. Specific Background: While various studies have examined EBS, there remains a lack of comprehensive analysis focused on the influence of demographic factors such as age and gender among doctors in diverse specialties. Knowledge Gap: Existing literature inadequately addresses the specific characteristics of EBS development across different age groups and professional roles, highlighting the need for targeted research in this area. Aims: This study aims to investigate the prevalence and developmental characteristics of EBS among doctors, with particular attention to variations by age and gender. Results: The findings indicate that female doctors aged 24 to 34 experience significantly higher overall stress levels compared to their male counterparts. Furthermore, women aged 46 to 55 demonstrated a pronounced resistance phase to stress. A weak direct correlation (p<0.05) was identified between the emergence of this resistance phase and the overall age of symptom development. Notably, over half of the respondents exhibited a resistance phase, while nearly 20% reported signs of stress and burnout. Oncologists and psychiatrists were found to have the highest prevalence of EBS. Novelty: This research provides new insights into the demographic factors influencing EBS, emphasizing the unique experiences of female medical practitioners and highlighting the specialties most affected. Implications: The findings underscore the necessity for healthcare institutions to implement targeted interventions to address EBS, particularly for vulnerable groups, thereby promoting the mental well-being of medical professionals and enhancing overall healthcare delivery.